Special Jurisdiction for Peace vs. Ordinary Jurisdiction: Competence Issues (2018)
The purpose of this paper is to demonstrate the contradictions, gaps and ambiguities that converge in the justice system subject of the Peace Agreementsigned between the Colombian government and the FARC-EP. An analytical and descriptive exposition is made of the dispositions that regulate the competence of the Special Jurisdiction for Peace, contained in the Final Agreement, the Legislative Act 01 of 2017, the Statutory Law that regulates it and the previous pronouncements made by the Constitutional Court. Initially, substantial issues are addressed regarding three areas of competence: temporal, material and personal ones. Afterwards the procedural difficulties are exposed, in which the differences between what was agreed, implemented and established by the Constitutional Court are made evident.